The Decolorization of Reactive Yellow Dye by Advanced Oxidation Using Continuous Reactors - Mohammed, Noor Abdul Ameer; I. Alwared, Abeer; S. Salman, Mohammed (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
The reactive yellow azo dye (λmax = 420 nm) is widely utilized for textile coloring due to its low-cost stability and tolerance properties. Treatment of dye-containing wastewater by traditional methods is usually inadequate because of its resistance to biological and chemical degradation. From this research, the continuous reactor of an advanced oxidation method supported the use of H2O2/TiO2/UV to remove the coloration of the reactive yellow dye from the discharge. At constant best conditions obtained from the batch reactor tests pH=7, H2O2 dosage = 400 mg/l and TiO2=25mg/l , the aqueous solutions were tested in the continuous reactor at different dye concentration and different flow rates . The maximum removal efficiency was found to be 91.552% obtained at the flow rate 5 l/h, also the results of decomposition information proved that method was pseudo-first-order kinetics.